Modified Variational Iteration Method for Solving Sedimentary Ocean Basin Moving Boundary Value Problem - M. M. Jawad, Umneya; S. Fadhel, Fadhel (Al-Nahrain Journal of Science, 2022)
The motion of the shoreline in sedimentary ocean basin were investigated and solved using the modified variational iteration method since it provides an efficient approximate solution of the problem under consideration, which appears to be accurate when the consecutive error between iterative solutions of the problem is evaluated. A diffusion equation with specified beginning and boundary conditions, with a moving interface type reflecting sediment transportation, is used to simulate the physical phenomena of sand particle migration in sea water. This article also discusses the shifting boundary value problem that occurs from shoreline change in a sedimentary ocean basin.